PENGARUH KONSEP TAZKIYATUN NAFS TERHADAP PRESTASI AKADEMIK SISWA SEKOLAH DASAR - Muhlasin, M Rifqi A'rof; atma, Atmadiharja; eri, Eri Kusumawati; siti, Siti Roudhotul Jannah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to understand how the concept of tazkiyatun nafs (purification of the soul) can influence the academic achievement of elementary school students. In Islamic teachings, tazkiyatun nafs is a fundamental principle that emphasizes spiritual and moral development from an early age. This research employs a qualitative approach and uses a case study method focused on fifth-grade students at SD Islam Assalam. Data were collected through direct classroom observations, in-depth interviews with Islamic Education teachers, and documentation of students’ academic scores. The findings reveal that the implementation of tazkiyatun nafs values in the teaching and learning process such as self-control, honesty, discipline, and patience positively impacts students’ learning motivation and academic performance. In other words, integrating spiritual values into primary education not only helps shape students' character but also significantly supports their academic achievement.